“Who Says that Male Writers Misrepresent Women?” Gender Perspectives from Nzeako’s Nkoli - Okide, Ujubonu J.; Okafor, Ebele Eucharia (NIU Journal of Humanities; Vol 11 No 1 (2026): NIU Journal of Humanities, Vol. 11 No. 1, March 2026DO - 10.58709/niujhu.v11i1.2470, 2026)
It is rife among feminists that male writers portray women negatively in their works. Much research has been carried out in this direction in both Literature written in English and that written in Igbo. However, much attention has not been paid to male-authored works to unravel and critique the idea of bias against women. Consequently, the present study questions the idea that in the novel Nkoli, written by a male JUT Nzeako, that female characters were negatively portrayed. This is with a view to finding out how the female characters were presented and perceived in the text. It was found that Nzeako went to great heights to present his female characters positively. Precisely, both protagonist and antagonist had good and sterling qualities in spite of their differences and conflict. Additionally, the female characters were perceived as motivators, industrious, advisers, important, as well as highlighting the value of the girl-child. The study is of the view that, at a deeper level of introspection and criticism, male writers are more interested in reflecting societal realities and therefore not biased in portraying their female characters. It is maintained that changes in the socio-cultural systems also corresponds with changes in the direction of writers, male or female. Keywords: Igbo novel, male writers, Nzeakọ, Nkọlị, gender, Patriarchy